1996
DOI: 10.1007/s004240050132
|View full text |Cite
|
Sign up to set email alerts
|

Calcium- and barium-dependent exocytosis from the rat insulinoma cell line RINm5F assayed using membrane capacitance measurements and serotonin release

Abstract: Electrophysiological measurements of cell capacitance (Cm) and biochemical assays of [3H] serotonin ([3H]5-hydroxytryptamine or [3H]5-HT) release were combined to study the control of secretion in rat insulinoma RINm5F cells. Depolarizing pulses produced Cm changes (DeltaCm), indicative of exocytosis, with the same voltage and Ca2+ dependency as the inward Ca2+ currents (ICa). Ba2+ was able to substitute for Ca2+ in stimulating exocytosis, but not endocytosis. However, both the relative potency and kinetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 57 publications
2
28
0
Order By: Relevance
“…Despite a relatively stable Ica (Fig. 1, Bi) there was a gradual depression of the secretory response in control cells, possibly due to depletion of readily releasable secretory granules [21,23,26]. The average values for three repetitive stimulations from 15 cells are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite a relatively stable Ica (Fig. 1, Bi) there was a gradual depression of the secretory response in control cells, possibly due to depletion of readily releasable secretory granules [21,23,26]. The average values for three repetitive stimulations from 15 cells are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there is evidence in both nerve terminals [2] and RINm5F cells [35] that not only the hormonal inhibition of release, but also its stimulation, could be achieved by the modulation of distal steps of the secretory process, downstream from second messenger production. We have recently found that while both exocytosis and endocytosis occur following Ca 2+ influx in RINm5F cells, substitution with Ba 2+ preferentially supports exocytosis [23], suggesting that the divalent ion sensitivities of the proteins involved in these two processes are different. Likewise, the observation at the single cell level that the adrenergic inhibition of exocytosis is not accompanied by an inhibition of endocytosis suggests that the proteins targeted by noradrenaline are specific to the exocytotic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 H-epinephrine can be loaded into PC12 cells in order to monitor secretion of 3 H-norepinephrine from permeabilized cells [12]. 3 H-serotonin release has been measured from preloaded clonal insulin-secreting RINm5F cells depolarized with KCl, but no correlation with insulin release was attempted [13]. Here, we show that 3 H-serotonin can be loaded into clonal pancreatic b-cells (INS-1) in order to monitor exocytosis from both intact and permeabilized cells validating the use of serotonin as a marker for insulin secretion.…”
Section: Introductionmentioning
confidence: 99%